Marxist political economy : essays in retrieval: selected works of Geoff Pilling - Pilling, Geoff (Routledge studies in the history of economics, 2013)
Geoff Pilling's work shows that Marxist theory is relevant to those struggling to understand the problems of capitalist society today, and that the work not only of Marx and Engels but that of later Marxist theorists, including Lenin is worth studying. It also shows that to understand the problems of today's society needs more than narrow specialist economic analysis, but a deep awareness of current developments in society.